Atomically Dispersed Bimetallic FeNi Catalysts as Highly Efficient Bifunctional Catalysts for Reversible Oxygen Evolution and Oxygen Reduction Reactions. Issue 13 (10th July 2019) - Cheng, Yi; He, Shuai; Veder, Jean‐Pierre; De Marco, Roland; Yang, Shi‐ze; Ping Jiang, San
Abstract: Bimetallic atomically dispersed FeNi catalysts anchored on N‐doped carbon nanotube with catalyst loading of 2–7 wt % with different Fe : Ni ratio have been developed as highly active and stable bifunctional catalyst for reversible oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) for metal air batteries via a modified one‐pot synthesis method. Compared with atomically dispersed single Fe and Ni catalysts, the bimetallic FeNi catalysts exhibit outstanding performance for reversible OER and ORR, achieving a low potential gap (Δ E ) of 0.81 V to deliver an OER current density of 10 mA cm −2 and an ORR current density of 3 mA cm −2 . The FeNi electrodes also show a much better stability in the cyclic tests, compared to that of the state‐of‐the‐art Pt/C and Pt/C+Ir/C electrodes for reversible OER and ORR. The high performance is likely due to the significantly enhanced OER activity contributed by the introduction of Ni atoms, forming bridged FeNi bimetallic dual atom active sites for OER. This study provides a new platform for the development of highly active bimetallic atomic catalysts based bifunctional electrocatalysts for metal‐air batteries. The modified one‐pot synthesis methods demonstrated in this study can also be applicable to other atomically dispersed catalysts on CNTs or graphenes. Abstract : Two metals, two reactions : Bimetallic atomically dispersed FeNi catalysts anchored on N‐doped carbon nanotube are shown as highly active and stable bifunctional catalyst for reversible oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) for metal air batteries via a modified one‐pot synthesis method.